Assessment of Nurses’ Knowledge and Competence in Managing Preeclampsia at Maternity Teaching Hospital in Sulaimani city - Amani Fadhil Abbas; Peshwaz Abdulrahman Ahmed; Nazera Salam Mena Qadir; Khanda Gharib Aziz (UHD Journal of Science and Technology)
Background: Preeclampsia is one of the most commonly reported complications during pregnancy, affecting approximately 2–15% of all pregnancies. It is characterized by the onset of hypertension after 20 weeks of gestation, accompanied by proteinuria, generalized edema, or evidence of organ dysfunction. This condition poses a serious threat to both maternal and fetal health, significantly increasing the risk of morbidity and mortality. According to the Centers for Disease Control and Prevention, “the number of pregnant women with high blood pressure has been increasing, with cases doubling from 1.8% in 2008 to 3.7% in 2021” reported in the United States. Risk factors for preeclampsia included race, advanced maternal age, obesity, null parity, multifetal pregnancy, and co-existing medical disorders. Managing preeclampsia is important because it can lead to complications for both the mother and baby. Aim: This study aimed to assess nurses’ knowledge and competence in managing preeclampsia at the Maternity Teaching Hospital in Sulaimani City. Materials and Methods: A cross-sectional descriptive study was conducted at Maternity Teaching Hospital in Sulaimani city, Iraq, from January 5, 2024, to June 13, 2024. The study included 25 nurses working in the emergency care unit and labor room of the Obstetrics and Gynecology Department. A questionnaire format was created according to the aim of the study and delivered by a team of five experts, consisting of two parts. Part one: The sociodemographic characteristics of the nurses, and the second part assessed their knowledge and practices regarding the management of preeclampsia data were collected through a structured face-to-face questionnaire and analyzed using the Statistical Package for the Social Sciences version 24. Results: The majority of nurses were over 35 years old, with a mean age of 36 (standard deviation = 12.86). In terms of education, most nurses held a diploma (48%), and 64% were married. Around 56% of nurses reported participating in workshops or programs related to preeclampsia in the obstetrics field. When asked to define eclampsia, 80% of the nurses answered correctly, and the same percentage correctly identified the best anticonvulsant for managing preeclampsia. Overall, the nurses demonstrated a fair level of knowledge in managing preeclampsia. No significant association was found between age and knowledge level, suggesting age did not influence knowledge or competency in managing preeclampsia. Conclusion and Recommendations: Based on the study’s findings, the nurses demonstrated a fair level of knowledge in managing preeclampsia, especially in treatment and prevention. To improve patient care and reduce maternal and fetal risks, addressing the gaps in nurses’ knowledge through regular training courses and educational programs is essential. These efforts will enhance their qualifications and ensure better care for women with preeclampsia.